Determining the Most Important Factors in House Design with Net Zero Energy Concept (Case study: Cluster X, Perumahan Y, Gading Serpong, Tangerang) - Budijanto Chandra; Samsu Hendra Siwi; Naniek Widayati Priyomarsono; Fermanto Lianto (Department of Architecture Universitas Muhammadiyah Jakarta, 2019)
The most significant environmental problem recently is global warming and causing environmental damage and threatening human life. It needs to immediately reduce CO₂ emissions from burning fossil fuels as a cause of global warming, and one way is to reduce the energy of fossil fuels in buildings and replace them with renewable energy. It is necessary to immediately apply the Net Zero Energy Building (NZE), which can significantly reduce the use of fossil fuels and use energy renewable. This study is to find out what needs to be considered in house design with NZE concepts in the context of tropical and humid climates such as in Jakarta and its surroundings. The method used is qualitative research with a case study approach. NZE buildings have the potential to be applied in by taking into account some of the NZE's house design guidelines.